2023
DOI: 10.4103/jfmpc.jfmpc_620_23
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the quality of life of GERD patients in the Aseer Region, Saudi Arabia

Mohammed A. Alzahrani,
Faisal S. Alamri,
Hatem M. Alshahrani
et al.

Abstract: Gastroesophageal reflux disease (GERD) is a common upper gastrointestinal disorder characterized by troublesome symptoms, including heartburn and acid regurgitation. GERD is associated with complications such as peptic stricture, Barrett's esophagus, and esophageal adenocarcinoma, and it negatively affects quality of life (QoL). Aims: To assess the factors influencing the QoL of GERD patients in the Aseer region of Saudi Arabia. Settings and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
(25 reference statements)
1
0
0
Order By: Relevance
“…On assessing the QOL of the study participants, we found that the non-GERD group had a significantly higher QOL regarding the physical, social, level of independence, overall QOL, and health perception; all showed a strong association with GERD (p < 0.05). These results were similar to many previous studies conducted in Saudi Arabia, which stated that GERD affects the physical state and daily activities of the patients [ 42 ]. In Turkey, a study published by Mungan [ 43 ] reported that GERD patients have a significantly lower QOL compared with the general population.…”
Section: Discussionsupporting
confidence: 92%
“…On assessing the QOL of the study participants, we found that the non-GERD group had a significantly higher QOL regarding the physical, social, level of independence, overall QOL, and health perception; all showed a strong association with GERD (p < 0.05). These results were similar to many previous studies conducted in Saudi Arabia, which stated that GERD affects the physical state and daily activities of the patients [ 42 ]. In Turkey, a study published by Mungan [ 43 ] reported that GERD patients have a significantly lower QOL compared with the general population.…”
Section: Discussionsupporting
confidence: 92%